Pengembangan Kompetensi Pedagogik Calon Guru melalui Program Magang dan Pengabdian kepada Masyarakat di SD Muhammadiyah Kota Ternate - Hariyanti Djafar; Sitti Ikwa M HI Asidu; Lidyasandra Lumatauw; Nurfaida Duwila; Hanisa Ipa; Yiping Eldiana Maga (Lembaga Yasin AlSys, 2026)
An internship program integrated with Community Service (PKM) is an important means of developing the professional competencies of prospective teachers while bridging the gap between theoretical knowledge and teaching practice in schools. This study aims to describe the process, dynamics, and outcomes of developing prospective teachers’ pedagogical competence through the implementation of an intensive internship and PKM program at SD Muhammadiyah Kota Ternate. This study employed a qualitative approach with a descriptive method. Data were collected through participatory observation, direct involvement in teaching practice, and document analysis during the implementation of the activities from May 6 to June 3, 2026. The results showed that the program improved prospective teachers’ skills in classroom management and in developing comprehensive teaching modules aligned with the Kurikulum Merdeka. Initial challenges, including students’ low levels of concentration and prospective teachers’ nervousness when teaching, were addressed through adaptive communication, the implementation of the Total Physical Response (TPR) strategy, and the use of interactive learning methods. This study concludes that the integration of internship and PKM programs plays an important role in strengthening prospective teachers’ pedagogical competence and social resilience through authentic learning experiences in the school environment. These findings provide practical implications for higher education institutions and partner schools in designing service-based internship programs that are more structured, reflective, and relevant to prospective teachers’ needs, while supporting the implementation of the Tri Dharma Perguruan Tinggi.